The Effect of Nutrition Education on Students’ Breakfast Habits and Academic Achievement at SMA Negeri 1 Sausu - Ni Luh Indrianti; Lilies; Abd. Hakim Laenggeng; Fatmah Dhafir; Syech Zainal; Musdalifah Nurdin (Bioscientist : Jurnal Ilmiah Biologi, 2026)
This study aimed to examine the effect of nutrition education on students’ breakfast habits and learning outcomes at SMA Negeri 1 Sausu, while also highlighting its role in promoting healthier breakfast behaviors among students. The study employed a quantitative approach using a one-group pretest-posttest design. The participants were 23 tenth-grade students selected through total sampling. Data were collected using questionnaires to assess students’ breakfast habits before and after the intervention, as well as documentation of students’ learning outcomes. Data were analyzed using descriptive quantitative analysis through mean scores, score improvement, and N-gain values. The results showed that the mean breakfast habit score increased from 40.09 in the pretest to 48.43 in the posttest, with an N-gain of 0.14, which was categorized as low. In addition, the mean learning outcome score increased from 77.30 before the intervention to 80.17 after the intervention, with an N-gain of 0.13, also categorized as low. These findings indicate that nutrition education contributed positively to improvements in students’ breakfast habits and learning outcomes, although the level of effectiveness remained low. Therefore, nutrition education has the potential to serve as a promotive and preventive strategy for fostering healthy breakfast behaviors and supporting academic improvement, provided that it is implemented continuously and supported by both the family and the school environment.